The role of energy in Turkey-Russian relations: Is it a dependency or necessity? - Atiş, Е.; Kapluhan, Е. (L. N. Gumilyov Eurasian National University, 2022)
Relations between Turkey and the Russian Federation have a rich historical heritage. Economic and trade relations constitute the driving force behind Turkish-Russian relations. Russia has been one of the most important trade partners of Turkey. Trade volume between the two states has reached 26,309 billion USD in 2019, with Turkey’s 3,854 billion USD worth of exports and 22,454 billion USD imports. A total number of 1972 projects with a total value of over 75,7 billion dollars have been realized so far by the Turkish contractors in Russia, while reciprocal investments have reached 10 billion dollars each. Energy constitutes one of the most important elements of relations between Turkey and Russia. With TurkStream and Akkuyu Nuclear Power Plant projects, cooperation in the field of energy is being carried further with Russia, which is among the leading energy suppliers. TurkStream Natural Gas Pipeline has been inaugurated on 8 January 2020.  Natural gas has the second-highest share in the Turkish energy mix at a rate of 32.5%. Nearly 55% of the natural gas is imported from one single source country, and nearly 85% of the current purchase agreements consist of long-term agreements that are based on the “take or pay” principle. The Russian gas and pipelines have critical importance in the natural gas supply of Turkey, and nuclear energy is being emphasized for the purpose of diversifying the resources. The share of nuclear energy in the Turkish energy mix is 0%, and the agreement in this field is made with Russia brings another dependency relation.
Keywords: 11. Sustainability; 7. Clean energy